Short Communication: Discovery of the Pig-Nosed Turtle (Carettochelys Insculpta) in the Jatiluhur Reservoir, Purwakarta, West Java - Muh. Sulaiman Dadiono (Indo Journal of Multidisciplinary Science, 2026)
The Pig-nosed turtle (Carettochelys insculpta) is a unique freshwater turtle species naturally distributed in southern Papua and Papua New Guinea. The presence of this species outside its natural habitat is a significant concern in conservation and invasive biology studies. This article aims to examine the presence of Carettochelys insculpta in the Jatiluhur Reservoir, Purwakarta, West Java, and the possible ecological impacts it may have on native species in the reservoir. Discovery data was obtained from an accidental catch by fishermen on December 14, 2025, using fishing nets in the Jatiluhur Reservoir. The research method used a desk study with data sources derived from scientific articles indexed by Google Scholar, online articles, and social media documentation on Facebook and TikTok related to the discovery of the species. Due to the lack of direct morphometric data, an estimation approach was carried out using Artificial Intelligence (AI) Gemini by analyzing the proportion of human hand size to the pig-nosed turtle's body in documentation photos. The analysis results showed that the individuals found had a Carapace Curve Length (CL) of approximately 45–55 cm, a Carapace Curve Width (CW) of approximately 35–45 cm, and a carapace diameter of approximately 40 cm, with an estimated total body length of 60–70 cm. These measurements indicate that the individuals were mature but had not yet reached the maximum size of the species. The presence of this species in the Jatiluhur Reservoir is suspected to be related to releases from the exotic or pet trade. The presence of C. insculpta has the potential to affect ecosystem balance through competition for space and food resources with local species, although further research is needed to determine the population status and its ecological impacts.